PENGARUH PENGELOLAAN KELAS DALAM PROSES BELAJAR MENGAJAR TERHADAP MINAT BELAJAR SISWA - John Boanerges Harefa; Bezisokhi Laoli; Wahyutra Adilman Telaumbanua; Yearning Harefa (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
Many teachers still face obstacles in managing their classes well, resulting in low student learning interest. This study aims to determine the effect of classroom management in the teaching and learning process on student learning interest at BNKP Luzamanu Private Junior High School. This study uses a quantitative approach. Data collection techniques are carried out through questionnaires that have been tested for validity and reliability. Data analysis is carried out using a simple linear regression test with the help of SPSS. The results of the study indicate that there is a significant influence between classroom management on student learning interest with a calculated t value of = 4.790 > t table = 2.101 at a significance level of 5%. Thus, it can be concluded that the better the classroom management carried out by teachers, the higher the student's learning interest.